Validation of the Persian Version of Occupational Coping Self-efficacy for Nurses Scale - Reza Rahimi; Ali Khodaei; Shokoufeh Mousavi (Iran University of Medical Sciences, 2022)
Background: Assessing the self-efficacy beliefs of Iranian nurses in coping with occupational stressors requires to have a reliable tool. This study aims to assess the validity and reliability of the short form of Occupational Coping Self-Efficacy for Nurses (OCSE-N) Scale for Iranian nurses. Methods: This is a methodological study. Participants were 151 nurses who were randomly selected from among those working in oncology wards of hospitals affiliated to Tehran University of Medical Sciences in 2021. The nurses completed the short form of OCSE-N and the Coping Inventory for Stressful Situations- Short Form (CISS-SF). This study employed exploratory factor analysis and Confirmatory Factor Analysis (CFA) to examine the factor structure of the Persian OCSE-N. The reliability was assessed by calculating Cronbach's alpha coefficients. The data were analyzed in AMOS and SPSS software v. 26. Results: The results of Principal Component Analysis by the Promax rotation and CFA showed that the Persian OCSE-N had two factors: 1) Coping self-efficacy to cope with the relational burden and 2) coping self-efficacy to cope with occupational burden. The correlation between subscales of OCSE-N and CISS-SF confirmed the convergent validity of the Persian OCSE-N. Cronbach's alpha coefficients for factors 1 and 2 were reported 0.75 and 0.77, respectively. Conclusion: The Persian OCSE-N is a valid and reliable tool to measure the perceived self-efficacy in coping with stressful situations among Iranian nurses.